UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 70% DAUN BELIMBING MANIS (Averrhoa carambola L.) DARI DESA TARUB TERHADAP BAKTERI Staphylococcus aureus - Dhanisa Dwi Nugrahanti; Gigih Kenanga Sari; Mingle A Pistanty (Joseph: Journal of Science and Pharmacy, 2023)
Background: Acne or acne vulgaris is ranked as the most common disease in the world, with a prevalence of 9.4% of the world's population. Staphylococcus aureus bacteria has a percentage of 79% in causing acne. The content of secondary metabolites in plants can act as an antibacterial with a strong mechanism of action. One of them is starfruit leaves (Averrhoa carambola L.) which contain antibacterial properties such as alkaloids, flavonoids, tannins. There are many populations of this plant in Tarub Village, Tawangharjo District, Grobogan Regency Purpose: To determine the antibacterial effectiveness of 70% ethanol extract of sweet starfruit leaves (Averrhoa carambola L.) obtained in Tarub village against Staphylococcus aureus bacteria Method: Leaves of starfruit (Averrhoa carambola L.) were extracted by maceration method with 70% ethanol solvent and antibacterial test by paperdisk method with concentration variances of 60%, 75% 90%. Results: Phytochemical screening of starfruit leaf extract (Averrhoa carambola L.) contains alkaloids, flavonoids, tannins, terpenoids and saponins. Antibacterial test of sweet starfruit leaf extract produced the largest inhibition zone diameter of 14.29 mm at a concentration of 60%. Conclusion: Leaf extract of sweet star fruit effectively inhibits the growth of Staphylococcus aureus bacteria.